Characteristics the Marshall Test Subsitutution of Polypropylene Plastic Pellets as Filler in Mixture Asphalt Concrete Binder Course (AC BC) - Mulyadi, Asri; Asrullah, Asrullah; Anggrainy, Rita; Irawan, Irawan; Rizal, Choirul (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
This research was carried out on a laboratory experimental scale, with the aim of determining the characteristics of the Marshall test for the substitution of Polypropylene plastic pellets in the Asphalt Concrete Binder Course (AC BC) mixture. The substitution of Polypropylene plastic pellets in AC BC mixture is 1%, 2%, 3% of the weight of filler in AC BC standard mixture. From the test results, it can be concluded that the characteristics of the marshall test include VMA values, VIM values, VFA values, stability values, flow values, MQ values that meet the predetermined requirements both without filler and with filler.